Securing the Belt and Road Initiative Risk Assessment, Private Security and Special Insurances Along the New Wave of Chinese Outbound Investments (Springer Singapore, 2018)
This collection, bringing together the views of a wide range of scholars, explores the expansion of Chinese outbound investments aimed to sustain the increased need for natural resources and how they have amplified the magnitude of a possible international crisis that the People's Republic of China may face in the near future. President Xi's Belt and Road initiative (BRI), aimed to promote economic development and exchanges with China for over 60 countries, necessitates a wide range of security procedures. While the threats to Chinese enterprises and Chinese workers based on foreign soil are poised to increase, there is an urgent need to develop new guidelines for risk assessment, special insurance and crisis management. While the Chinese State Owned Enterprises are expanding their international reach capabilities, they still do not have the capacity to assure adequate security and demonstrate corporate social responsibility. In such a climate, this collection will be of profound value to policy makers, those working in the financial sector, and academics.